C60 Fullerenes Suppress Reactive Oxygen Species Toxicity Damage in Boar Sperm - Li, Xinhong; Wang, Lirui; Liu, Huan; Fu, Jieli; Zhen, Linqing; Li, Yuhua; Zhang, Yaozhong; Zhang, Yafei (Nano-Micro Letters, 2019)
We report the carboxylated C60 improved the survival and quality of boar sperm during liquid storage at 4 °C and thus propose the use of carboxylated C60 as a novel antioxidant semen extender supplement. Our results demonstrated that the sperm treated with 2 μg mL−1 carboxylated C60 had higher motility than the control group (58.6% and 35.4%, respectively; P ˂ 0.05). Moreover, after incubation with carboxylated C60 for 10 days, acrosome integrity and mitochondrial activity of sperm increased by 18.1% and 34%, respectively, compared with that in the control group. Similarly, the antioxidation abilities and adenosine triphosphate levels in boar sperm treated with carboxylated C60 significantly increased (P ˂ 0.05) compared with those in the control group. The presence of carboxylated C60 in semen extender increases sperm motility probably by suppressing reactive oxygen species (ROS) toxicity damage. Interestingly, carboxylated C60 could protect boar sperm from oxidative stress and energy deficiency by inhibiting the ROS-induced protein dephosphorylation via the cAMP-PKA signaling pathway. In addition, the safety of carboxylated C60 as an alternative antioxidant was also comprehensively evaluated by assessing the mean litter size and number of live offspring in the carboxylated C60 treatment group. Our findings confirm carboxylated C60 as a novel antioxidant agent and suggest its use as a semen extender supplement for assisted reproductive technology in domestic animals. Highlights: 1 Carboxylated C60 may be considered a novel antioxidant agent to be used as a semen extender supplement for assisted reproductive technology. 2 Carboxylated C60 could enhance the motility parameters and characteristics of boar spermatozoa during liquid storage at 4 °C and protect boar sperm from oxidative stress by inhibiting the reactive-oxygen-species–induced protein dephosphorylation. 3 Novel insights into the molecular mechanisms contributing to the protective effects of carboxylated C60 are provided.